Electromyographic analysis of the three subdivisions of gluteus medius during weight-bearing exercises - O'Sullivan Kieran; Smith Sharon M; Sainsbury David (BMC, 2010)
Abstract Background Gluteus medius (GM) dysfunction is associated with many musculoskeletal disorders. Rehabilitation exercises aimed at strengthening GM appear to improve lower limb kinematics and reduce pain. However, there is a lack of evidence to identify which exercises best activate GM. In particular, as GM consists of three distinct subdivisions, it is unclear if GM activation is consistent across these subdivisions during exercise. The aim of this study was to determine the activation of the anterior, middle and posterior subdivisions of GM during weight-bearing exercises. Methods A single session, repeated-measures design. The activity of each GM subdivision was measured in 15 pain-free subjects using surface electromyography (sEMG) during three weight-bearing exercises; wall squat (WS), pelvic drop (PD) and wall press (WP). Muscle activity was expressed relative to maximum voluntary isometric contraction (MVIC). Differences in muscle activation were determined using one-way repeated measures ANOVA with post-hoc Bonferroni analysis. Results The activation of each GM subdivision during the exercises was significantly different (interaction effect; p < 0.001). There were also significant main effects for muscle subdivision (p < 0.001) and for exercise (p < 0.001). The exercises were progressively more demanding from WS to PD to WP. The exercises caused significantly greater activation of the middle and posterior subdivisions than the anterior subdivision, with the WP significantly increasing the activation of the posterior subdivision (all p < 0.05). Discussion Posterior GM displayed higher activation across all three exercises than both anterior and middle GM. The WP produced the highest %MVIC activation for all GM subdivisions, and this was most pronounced for posterior GM. Clinicians may use these results to effectively progress strengthening exercises for GM in the rehabilitation of lower extremity injuries.